Chronic nicotine differentially alters cocaine-induced locomotor activity in adolescent vs. adult male and female rats - Collins, Stephanie L; Izenwasser, Sari (Neuropharmacology, 2004)
Tobacco use is prevalent in the adolescent population. It is a major concern because tobacco is highly addictive and has also been linked to illicit drug use. There is not much research, however, on the interaction between nicotine and other stimulant drugs in animal models of early adolescence. This study examined the effects of chronic nicotine alone and on cocaine-stimulated activity in male and female periadolescent rats compared to male and female adult rats. During the seven-day nicotine pretreatment period, nicotine increased locomotor activity in all groups compared to vehicle controls. Male and female adult rats and female periadolescent rats developed sensitization to the locomotor-activating effects of nicotine over the 7-day treatment period, while male periadolescent rats did not. All groups treated with nicotine, however, exhibited sensitization to nicotine-induced repetitive motion over the 7-day nicotine treatment period. On day 8, male periadolescent rats pretreated with nicotine were more markedly sensitized to the locomotor-activating effects of cocaine than male adult rats, while female rats pretreated with nicotine were not sensitized to cocaine. In contrast, male and female periadolescent rats, but not adult rats, had increased amounts of repetitive beam breaks induced by cocaine after nicotine pretreatment. Overall, it appears that cross-sensitization to cocaine is greater in periadolescent than in adult rats, and that males are more sensitized than females. Thus, it may be that nicotine use during adolescence carries a greater risk than during adulthood and that male adolescents may be particularly vulnerable to the risk of cocaine abuse after nicotine use. This information should be taken into account so as to help us better understand the development of drug addiction in adolescents compared to adults.